PP.09.26: AMBULATORY BLOOD PRESSURE MONITORING-DERIVED SHORT-TERM BLOOD PRESSURE VARIABILITY IN PRIMARY ALDOSTERONISM. (June 2015) - Grillo, A.; Bernardi, S.; Rebellato, A.; Fabris, B.; Bardelli, M.; Burrello, J.; Rabbia, F.; Veglio, F.; Fallo, F.; Carretta, R.
Abstract : Objective: The aim of our study was to investigate the ambulatory blood pressure monitoring (ABPM)-derived short-term BP variability (BPV) in patients with primary aldosteronism (PA), either idiopathic hyperaldosteronism (IHA) or aldosterone-producing adenoma (APA), in comparison with patients with essential hypertension (EH) and normotensive (NT) controls. Design and method: Thirty PA patients (16 IHA, 14 APA), 30 EH patients and 30 NT, matched for sex, age, BMI and antihypertensive therapy, were studied. Short-term BPV was derived from ABPM and calculated as the following: (1) standard deviation (SD) of 24-h, daytime, and nighttime BP; (2) 24-h weighted SD of BP; and (3) average real variability (ARV), i.e., the average of the absolute differences between consecutive BP measurements over 24 h. Results: Standard Deviation (SD) of 24-h, daytime and nighttime BP, 24-h weighted SD of BP, and 24-h BP ARV were not different between PA and EH patients (P ns). All BPV indices were higher in PA, either IHA or APA subtypes, and EH patients, compared to NT (P < 0.001 to P < 0.05). Conclusions: ABPM-derived short-term BPV is increased in PA patients, and it may represent an additional cardiovascular risk factor in this disease. The role of aldosterone excess in BPV has to be clarified.